Age Diversity among Faculty Members of MSU-Sulu College of Education: Its Impact on Their Teaching Efficiency - Anuddin, Fermina O. (HM Publisher, 2022)
Unmanaged age diversity in the workplace might become an obstacle to achieving organizational goals. This study was aimed to identify the age profile, teaching efficiency rating (TER), and significance difference between the efficiency of senior and junior faculty members of teachers in MSU-Sulu, College of Education. This study utilized the quantitative method of research where the teaching efficiency rating of both senior and junior faculty members rated by their students was tabulated and interpreted. The research instrument used is the teaching efficiency rating (TER) of the teachers where students are raters. This study employs random sampling where teachers were selected randomly. Data were analyzed with SPSS version 25.0. Based on results, it was found out that age does not interfere with teacher efficiency in teaching. Both senior and junior faculty members of the college of education are performing at their utmost potential, whether they are young or old members of the institution of higher learning. Stereotypes on senior faculty might not exist in the College of Education.